Reform of Arabic Syntax by Mahdi Al-Makhzumi: Foundations and Aspects - Mohd Nizwan Musling (Usuli Faqih Research Centre PLT., 2024)
Al-Qanatir International Journal of Islamic Studies Vol. 32 No. 2 (page:226–241)